IMPLIKASI PIJAT BAYI TERHADAP PENINGKATAN BERAT BADAN PADA BAYI USIA 6-8 BULAN - Prodalima Sinulingga; Delfriana Ayu A (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Infant massage has been practiced almost all over the world since ancient times, including Indonesia. Baby massage art is taught hereditary although it is not known clearly how massage and touch can have a positive effect on the human body. Baby massage can be classified as a touch stimulation application, because in the baby massage there is a touch element in the form of affection, attention, voice or speech, eye sight, movement, and massage. This stimulation will stimulate the development of the structure and function of brain cells. This research type is quantitative by using Quasi Experimental design without control group with One Group Pre Test and Post Test Design method. Researchers made treatment of one study subject alone, by performing pre-test and post-intervention testing. This research was conducted in Kute Bakti, Babul Makmur Subdistrict, Southeast Aceh Regency. The sampling technique using total sampling technique thus, the researchers took a sample of the entire population of as many as 12 babies. The result of this study showed that based on the age of the infant, the age of 8 months was 6 people (50%), 7 months old 4 people (37,5%) and age 6 months, 2 (16,7%). Based on the sex of the baby, the most male sex is as many as 8 people (66.6%) and women as many as 4 people (33.3%). Based on the education of parents, most high school education that is as much as 7 people (58.3%) and junior high as 5 people (41.7%). The test results obtained value P = 0.07 (P <0.05) in other words there is ingcraesing baby's weight after the baby massage therapy with the average weight baby weight of 1.05 kg. The results showed that the use of infant massage therapy has implications for infant weight gain, therefore the results of this study is expected to be information and input for educational institutions and nursing professions, especially nursing children and nursing maternity as well as evidence base in improving the baby's weight both in theory or practice. Keywords: Baby Massage, Weight Gain